Penerapan Participatory Ergonomics dalam Perancangan Ulang Permainan Buggy untuk Meningkatkan Keselamatan bagi Pengguna: Studi Kasus di Kampung Gajah Wonderland - Sukapto, Paulus; Samanta, Handy (Universitas Ahmad Dahlan, 2019)
Background: The Gajah Wonderland Kampong is a recreation area offering various games that is located in Lembang, Bandung. The favorite game to be played in this park is the so-called Buggy Game. The results of in-depth observations and close examination indicate that this particular Buggy Game is not ergonomic and that path information is inadequate so that accidents often occur. In order to solve these problems, the Participatory Ergonomics (PE) method has been employed. Method: The implementation of PE involves key stakeholders, namely the management in charge, workers, designers, and ergonomics experts. The stakeholders have discussed these matters to reach an agreement in the shape of a design that suits the user. Results: This study resulted in a chair design concept that can be adjusted according to needs, a gas pedal limiting design, a track plan design and manufacturing directions, a speed sensor design and an emergency button, in addition to a head frame design, and a design for anti-heat material in the engine area. Conclusion: PE turns out to be the right method for repeated repairs or improvements made to the Buggy Game because it involves the main user so as to produce a design that is able to improve both the comfort and safety of the users.